LIKUIDITAS SEBAGAI PREDIKTOR PROFITABILITAS: SEBUAH STUDI EMPIRIS PADA PERUSAHAAN SEKTOR INDUSTRI MANUFAKTUR - Powell Gian Hartono; Henny Setyo Lestari; Richy Wijaya; Agus Budi Hartono; Georgina Maria Tinungki (Derivatif : Jurnal Manajemen, 2020)
The purpose of this study is to examine the effect of liquidity with proxies are the current ratio (CR), and the quick ratio (QR) to profitability with proxies are the return on assets (ROA) and the return on equity (ROE), on manufacturing sector companies listed on the Indonesia Stock Exchange with the research periods are 2014 - 2018. The purposive sampling method was used, and as many as twenty companies were sampled. The test uses multiple linear regression analysis; the stage are classical assumption test, the goodness of fit test, F-test, and T-test. The results obtained in the first model with ROA as the criterion are CR and QR as the significant predictors. The results obtained in the second model with ROE as the criterion is QR as the significant predictor, while CR has no significant effect to ROE. These results indicate that each profitability ratio is specifically influenced by the respective liquidity ratios studied so that companies can pay more attention to matters related to these variables in order to support efforts to increase company profitability.Keywords: Current Ratio, Manufacturing Company, Return on Assets, Return on Equity, Quick Ratio